PENGARUH KOMPOSISI ASH BATUBARA TERHADAP KUALITAS KLINKER PORTLAND CEMENT PADA PT. SEMEN TONASA UNIT III - Nurlianti Dahliar; Sri Widodo; Adi Tonggiroh (Jurnal Penelitian Geosains, 2014)
Portland cement clinker is a hydraulic material consists of C3S, C2S, C3A and C4AF. For producing clinker, raw meal have been burn in kiln at temperature 1450oC by using the heat combustion from coal. Clinker burning process is the most important process for the cement industry. In the portland cement industry, coal was not only used as a fuel, but it can also affected the composition of clinker. The coal ash will be mixed with raw meal during clinkerization process. Therefore, when the quality of the coal is not in accordance with the raw meal, it will cause crude clinker. The main purpose of study is to determine the influence of coal ash toward clinker quality. It should be known because portland cement clinker quality of PT. Semen Tonasa have to be on standard according to ASTM C-150-1999 and SNI No. 15-6514-2001. The results of paired T-test analysis showed that the composition of the coal ash which affected the quality of clinker after clinkerization process were LSF, SM, C3S, C2S, and C4AF. Based on the result of simple regression analysis, the amount of coal ash composition toward clinker portland cement quality was minor. LSF had the highest influence up to 0.885%, AM range between 0.1-0.3%, C2S range between 0.01-0.07%, C3S range between 0.01-0.02%, and C4AF was 0.019%.Keywords: clinker, coal ash, quality, C3S, C4AF, portland cement